A genetic-based algorithm for recovery: A pilot study - Pickering, Craig; Kiely, John; Suraci, Bruce; Quigley, Charlie; Watson, Jake (bioRxiv, 2017)
Exercise training creates a number of physical challenges to the body, the overcoming of which drives exercise adaptation. The balance between sufficient stress and recovery is a crucial, but often under-explored, area within exercise training. Genetic variation can also predispose some individuals to a greater need for recovery after exercise. In this pilot study, 18 male soccer players underwent a repeated sprint training session. Countermovement jump (CMJ) heights were recorded immediately pre- and post-training, and at 24- and 48-hours post-training. The reduction in CMJ height was greatest at all post-training time points in subjects with a larger number of gene variants associated with a reduced exercise recovery. This suggests that knowledge of genetic information can be important in individualizing recovery timings and modalities in athletes following training.